Answer:
The point-slope form of the equation with slope of one half and passing through point (6, -3) is: y +3 = one half(x - 6).
Explanation:
The general formula for point-slope form is (y-y,) = m(x-x,) where m= slope and (x, , y,) represents a point on the line. In order to find the equation the represents the line given, you simply need to fill in the variables 'm', 'x,' and 'y,' with the values given. In this case (6, -3) means x, = 6 and y, = -3 and slope is one half. (y - (-3)) = one half (x - 6) or simplified (y + 3) = one half (x -6).